ACTIVITY OF POLYHERBAL EXTRACT AGAINST BACTERIA CAUSING SKIN INFECTIONS IN DIABETIC PATIENTS. - Kota, Chaitanya Sravanthi; HEMANTH KUMAR V; SUNITHA REDDY M (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective : - The objective of this study is to evaluate antibacterial activity of Polyherbal extract on few microorganisms causing skin infections in most of the diabetic patients . Methods : - Methanolic Polyherbal extract was prepared from Acacia ferruginia (bark & fruit), Chloroxylon swietenia (bark, leaf, root), Casearia elliptica (bark), Terminalia alata (root, leaf). The preliminary phytochemical analysis was performed to identify the major phytoconstituents in the extract. Polyherbal extract was evaluated for antibacterial activity against bacteria like Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli, Proteus species, Klebsiella species causing skin infections , diabetic foot infections in diabetic patients. In-vitro method of agar diffusion disc method was used for the evaluation of antibacterial activity through zone of inhibition. The standard drug used was Gentamicin. Minimum Inhibitory Concentration (MIC) of the extract was done using broth dilution method. Results: The polyherbal extract showed good antibacterial activity. The standard drug used was Gentamicin. The Methanolic Polyherbal extract showed potent activityon all the selected microorganisms. The Polyherbal extract was active against Pseudomonas aeruginosa (2.57 + 0.39) and E.coli (2.92 + 0.29) when compared with standard. The polyherbal extract showed potent activity on Bacillus subtilis and Proteus vulgaris. Conclusion : The polyherbal extract showed broad spectrum activity by being active against gram positive and gram negative microorganisms providing the scope for further analysis as a antibacterial preparation for the skin infections in diabetes patients.